Demographic and Socioeconomic Differences in Outpatient Ophthalmology Utilization in the United States - Rasendran, Chandruganesh; Tye, George; Knusel, Konrad; Singh, Rishi P. (American journal of ophthalmology, 2020)
The purpose was to assess differences in outpatient ophthalmologic usage based on patient characteristics such as race/ethnicity, income, insurance type, geographical region, and educational attainment. Retrospective cross-sectional study. The Medical Expenditure Panel Survey (MEPS) is a nationally representative data set for the noninstitutionalized population cosponsored by the Agency for Healthcare Research. This study involved 183,054 MEPS respondents from 2007 to 2015. Primary outcome measure was patient utilization of outpatient ophthalmologic care. Secondary outcome measure was annual health care use and costs by patients in outpatient, inpatient, and the emergency department settings based on race. Overall, 21,673 participants self-reported an ophthalmologic condition, and 12,462 had at least 1 outpatient ophthalmologic visit. Hispanic (adjusted odds ratio [aOR] 0.72; P < .001) and black patients (aOR 0.74; P < .001) had fewer outpatient visits than their non-Hispanic white counterparts. Uninsured (aOR 0.41; P = .009) and Medicare/Medicaid (aOR 0.92; P < .001) patients had less outpatient care than their privately insured counterparts. Increasing income and education was associated with higher outpatient ophthalmologic care utilization. In the emergency department, non-Hispanic white patients had the least encounters (1.1 per 100 patients) and highest costs ($25,314.05) when compared to non-Hispanic black patients (3.2 encounters per 100 patients and $10,780.22 respectively) and Hispanic patients (2.2 encounters per 100 patients and $9,837.03 respectively). This study's findings demonstrate differences in outpatient ophthalmologic utilization based on demographic and socioeconomic characteristics. Concurrently, minority Americans had more ophthalmic emergency department visits but lower cost per visit. There is a need to further characterize these differences to predict future ophthalmologic care needs. •Demographically disadvantaged Americans had fewer outpatient ophthalmologist visits.•Geographically, Americans in the Midwest and West had less outpatient utilization.•Minority Americans had more ophthalmic emergency department visits but lower cost per visit.•Current models may not be sufficient for expected population demographic changes.•Further characterization of these results is needed to better predict future needs.